2018
DOI: 10.1002/jlb.5a0717-291rrr
|View full text |Cite
|
Sign up to set email alerts
|

CD71+ erythroid cells from neonates born to women with preterm labor regulate cytokine and cellular responses

Abstract: Neonatal CD71+ erythroid cells are thought to have immunosuppressive functions. Recently, we demonstrated that CD71+ erythroid cells from neonates born to women who underwent spontaneous preterm labor are reduced to levels similar to those of term neonates; yet, their functional properties are unknown. Herein, we investigated the functionality of CD71+ erythroid cells from neonates born to women who underwent spontaneous preterm or term labor. CD71+ erythroid cells from neonates born to women who underwent spo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
22
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 80 publications
4
22
2
Order By: Relevance
“…In agreement, a very recent report indicated that CD71 + erythroid cells from human cord blood inhibited CD4 + and CD8 + T cells proliferation and reduced CD62L expression in activated T cells (27). In contrast, this study claimed that CD71 + erythroid cells enhanced proinflammatory cytokine production in vitro (27). The explanation for this discrepancy might be due to multiple factors such as the study population (African American women versus white women), using different bacterial strains for the cell stimulation, and isolation techniques for CD71 + erythroid cells (positive versus negative selection).…”
supporting
confidence: 88%
See 1 more Smart Citation
“…In agreement, a very recent report indicated that CD71 + erythroid cells from human cord blood inhibited CD4 + and CD8 + T cells proliferation and reduced CD62L expression in activated T cells (27). In contrast, this study claimed that CD71 + erythroid cells enhanced proinflammatory cytokine production in vitro (27). The explanation for this discrepancy might be due to multiple factors such as the study population (African American women versus white women), using different bacterial strains for the cell stimulation, and isolation techniques for CD71 + erythroid cells (positive versus negative selection).…”
supporting
confidence: 88%
“…Furthermore, we have shown that CD71 + erythroid cells form full-term cord blood specimens, have immunosuppressive properties, and suppress proinflammatory cytokines (IL-6 and TNF-a) by myeloid cells (23) and also inhibit T cell proliferation (24). In agreement, a very recent report indicated that CD71 + erythroid cells from human cord blood inhibited CD4 + and CD8 + T cells proliferation and reduced CD62L expression in activated T cells (27). In contrast, this study claimed that CD71 + erythroid cells enhanced proinflammatory cytokine production in vitro (27).…”
supporting
confidence: 74%
“…Growing evidence shows that neonatal immunity depends on the critical immunosuppressive function of CD71+ nucleated erythroid cells (60)(61)(62)(63)(64)(65). Indeed, we have shown that cord blood CD71+ erythroid cells play a central role in the modulation of inflammatory responses of neonates, which may be defective in those delivered prematurely (66,67). Therefore, we investigated whether prenatal maternal stress alters the number of CD71+ erythroid cells in neonates (Figure 6A).…”
Section: Prenatal Maternal Stress Does Not Alter Neonatal Cd71+ Erythmentioning
confidence: 99%
“…CD71+ erythroid cells have immunomodulatory functions on cord blood leukocytes (157)(158)(159), and that their direct contact with maternal peripheral immune cells increases the secretion of pro-inflammatory mediators by such cells (159). Therefore, it is likely that the trafficking of CD71+ erythroid cells from the fetus into the mother directly affects maternal immune responses (159).…”
Section: Erythroid Cells In the Maternal Circulation During Normal Prmentioning
confidence: 99%